2006
DOI: 10.1007/s00431-006-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Two decades’ experience of renal replacement therapy in paediatric patients with acute renal failure

Abstract: During the past 20 years, childhood renal replacement therapy (RRT) and the treatment of underlying diseases experienced extensive advances. We reviewed the data of our critically ill patients with acute renal failure (ARF) and RRT, comparing two decades from 1985 to 1994 and from 1995 to 2004. There were 87 patients with a mortality rate of 45% in the first decade, decreasing to 28 patients with a mortality rate of 39% in the second decade. The mortality rate decreased from 51% to 20% in patients older than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Factors associated with a higher mortality rate are clinical severity, underlying disease, and-above all-the hemodynamic status at the start of therapy [4][5][6][7][8][9][10][11]. Some studies have found a higher mortality rate among children with heart disease than among other patients requiring CRRT, particularly in those undergoing cardiac surgery [5,8].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Factors associated with a higher mortality rate are clinical severity, underlying disease, and-above all-the hemodynamic status at the start of therapy [4][5][6][7][8][9][10][11]. Some studies have found a higher mortality rate among children with heart disease than among other patients requiring CRRT, particularly in those undergoing cardiac surgery [5,8].…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have analyzed prognostic factors in critically ill children who develop renal failure and/or require RRT. Clinical severity, hemodynamic disturbances, number of organ failures, and a positive fluid balance before starting treatment are the main factors determining the prognosis in these patients [4][5][6][7][8][9][10][11]14]. Critically ill children treated using RRT often require relatively prolonged treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have described the individual AEs, safety and usefulness of CRRT in critically ill patients over the last decade [15,17,18] , especially in children [17,[19][20][21] . However, very few studies systematically investigated the incidence of CRRT-related AEs in adult populations, including hemodynamic instability, electrolyte disturbances, coagulopathy and others [15][16][17]22] . It is also often difficult to distinguish between AEs related to CRRT and those related to comorbid conditions or the critical illness itself [23].…”
mentioning
confidence: 99%
“…Mortality rates stratified by dialysis modality in children have remained fairly constant in the past decades, with an overall mortality rate of around 45%, ranging from 27 to 62% (1)(2)(3)(4). The better survival rate for hemodialysis (HD) found in the study by Bunchman et al (1) was attributed to a preselection of more hemodynamically stable patients for HD.…”
Section: Introductionmentioning
confidence: 99%